Cost-Effective ERT Technique for Oil-in-Water Measurement for Offshore Hydrocyclone Installations. Issue 6 (2015) - Durdevic, Petar; Hansen, Leif; Mai, Christian; Pedersen, Simon; Yang, Zhenyu
Abstract: The goal of this paper is to introduce and design a cost-effective Oil-in-Water (OiW) measuring instrument, which will be investigated for its value in increasing the efficiency of a deoiling hydrocyclone. The technique investigated is based on Electrical Resistivity Tomography (ERT), which basic principle is to measure the resistivity of substances from multiple electrodes and from these measurements create a 2-D image of the oil and gas component in the water. This technique requires the measured components to have different electrical resistances, such as seawater which has a lower electrical resistance than hydrocarbon oil and gas. This work involves construction of a pilot plant, for testing the feasibility of ERT for OiW measurements, and further exploring if this measured signal can be applied as a reliable feedback signal in optimization of the hydrocyclone's efficiency. Different algorithms for creating 2-D images and the feasibility of estimating OiW concentrations are studied and evaluated. From both steady state and continuous laminate flow perspectives, with respect to the objective which is to use this measurement for feedback control purposes.